Gymnastics: Techniques used in high-scoring and low-scoring 'Roche' vaults performed by elite male gymnasts - Takei, Y.; Dunn, J. H.; Blucker, E. (Sports Biomechanics, 2003)
The 16 highest-scored Roche vaults (GI) performed during the 2000 Olympic Games were compared with those receiving the 16 lowest scores (G2). A 16-mm motion picture camera operating at 100 Hz recorded the vaults during the competition. The results of t tests (p< .05) indicated G1, compared to G2, had (a) shorter time of board support, greater normalised average upward vertical force and backward horizontal force exerted by the board, greater change in the vertical velocity while on the board, and greater vertical velocity at board take-off, (b) comparable linear and angular motions in pre-flight, (c) smaller backward horizontal impulse exerted by the horse, smaller loss of the horizontal velocity while on the horse, and greater horizonal and vertical velocities at horse take-off, (d) greater height and larger horizontal distance of post-flight, (e) higher body mass centre at knee release, and (f) higher mass centre, greater normalised moment of inertia, and smaller vertical velocity at mat touchdown. Therefore, gymnasts and coaches should focus on sprinting the approach; blocking and pushing of the take-off board rapidly and vigorously; departing the board with a large vertical velocity; exerting large downward vertical force and small forward horizontal force from the handstand postion while on the horse; departing the horse with large horizontal and vertical velocities and completing the majority of the double salto near the peak of trajectory and releasing the knees above the top of the horse to prepare for a controlled landing.